Music therapy as a non-pharmacological intervention for persons living with dementia: client assessment and types of music therapy interventions - Desai, Sachin V. (International Journal Of Community Medicine And Public Health, 2024)
Geriatric giants account for the five most prevalent morbidities that cause immense decline in functional capacity and decreased quality of life. Immobility, instability leading to falls and fractures, incontinence, impaired cognition (dementia) and iatrogenesis affect majority of the ageing elderly leading to dependency, caregiving and associated burden among caregivers. Concept of non-pharmacological interventions in dementia care: interventions that involve non-pharmacological (non-medicinal) measures, have proven benefits to the people living with dementia (PLWD). music therapy, nature therapy that involves nature walks and living amidst natural spaces, have shown to have immense biophilia effects on the various organ systems in the human body. Immense health benefits have been documented among PLWD: dawn phenomenon is a clinical phenomenon where the PLWD experiences agitation, aggression and loud speech in the evenings associated with dementia. Out of all the seven studies published, there were significant improvements in mood, reduction in aggressive behavior, improving anxiety symptoms, reducing caregiver burnout and improving overall quality of life of the people living with dementia and their caregivers. With promising results among various interventional studies across the world, NPI is an important intervention with minimal to nil side effects with long term benefits on frequent administration.